Learning and teaching by literature. "Casus" of Polish romanticism created in country - Dominika Gruntkowska (Studia z Teorii Wychowania)
This article is devoted to the issue of one of the methods of informal education in the Romantic period, namely literature. Polish modern national consciousness was formed during the partitions, and the place of its formation was the émigré literature. The ideas flowing from it penetrate into the literature created in the country, the latter being more involved in the creation and dissemination of national patterns in society. The issue of imitating in domestic literature the patterns developed by bards is also raised.